Microbiological and physicochemical characteristics of bakasang laor, a traditional fermented fishery product from Maluku, Indonesia - Ferymon Mahulette; TRI SANTI KURNIA (Society for Indonesian Biodiversity, 2020)
Abstract. Mahulette F, Kurnia TS. 2020. Microbiological and physicochemical characteristics of bakasang laor, a traditional fermented fishery product from Maluku, Indonesia. Biodiversitas 21: 2216-2223. Bakasang laor consisted of two types, i.e. with and without vinegar. The microbiological research of bakasang processed use laor as raw material is very limited therefore these investigations are necessary to be conducted. The research aimed to analyze the microbiological and physicochemical characteristics of two types of bakasang laor. The microbiological characteristics are used to determine product safety whereas the physicochemical characteristics, amino acids, and fatty acids contents can determine the nutritional value for consumption. The sample of bakasang laor was taken from traditional producers in Latuhalat, Ambon. Microbiological analysis using plate count method. From the measurement, the total number of halotolerant and coliform bacterial in bakasang laor without vinegar were 6.2 log CFU/g and 6.5 log CFU/g, respectively, while the total of lactic acid bacteria in bakasang laor with vinegar was 6.6 log CFU/g at the end of fermentation. The total amino acids and fatty acids contents of bakasang laor without vinegar at the end of fermentation were 11.25% and 32.23%, while bakasang laor vinegar was 9.38% and 32.72%, respectively. The bacteria found in bakasang laor were Leuconostoc mesenteroides, Bacillus subtilis, Staphylococcus arlettae, Staphylococcus petrasii, Escherichia coli, and Enterobacter cloacae. Generally, microbiological and physicochemical characteristics of bakasang laor with vinegar were better than bakasang laor without vinegar. This research can improve the quality of this fermentation product in the future.